In Vivo Efficacy of Trovafloxacin against Bacteroides fragilis in Mixed Infection with either Escherichia coli or a Vancomycin-Resistant Strain of Enterococcus faecium in an Established-Abscess Murine Model - Stearne, Lorna E. T. (American Society for Microbiology, 2001)
The pharmacodynamic and pharmacokinetic properties of trovafloxacin were studied in a standardized murine model of established subcutaneous abscesses. Daily dosing regimens of 37.5 to 300 mg/kg every 8 h (q8h) or every 24 h (q24h) were started 3 days after inoculation with mixtures containing either Bacteroides fragilis-Escherichia coli-autoclaved cecal contents (ACC) or B. fragilis–vancomycin-resistant Enterococcus faecium (VREF)–ACC. Treatment was continued for 3 or 5 days. The efficacy of treatment was determined by the decrease in abscess bacterial counts and abscess weights, as well as by the reduction in inflammation (biodistribution of (99m)Tc-HYNIC immunoglobulin G) compared to saline-treated controls. Trovafloxacin showed a significant dose-response effect on the bacterial counts, weight, and inflammation of B. fragilis-E. coli abscesses after 3 and/or 5 days of treatment. A maximum 3.4 and 3.1 log(10) reduction in CFU/abscess in the respective B. fragilis and E. coli bacterial counts was attained after 5 days of treatment with daily doses of 300 mg/kg. The peak serum concentration was more predictive for effect than the area under the concentration-time curve. The C(max) was the pharmacodynamic index most predictive for success, and the efficacy of the q24h regimens was significantly better than the q8h regimens. The antibiotic was ineffective against the VREF in mixed infection with B. fragilis, while the killing of the anaerobe in the same combination was significantly less than in the E. coli combination (P < 0.05). We conclude that this is a useful model for studying the activity of antimicrobials for the treatment of small (<1-cm), undrainable, mixed-infection abscesses. In addition, we have shown for the first time that a decrease in bacterial numbers also leads to a reduction in both abscess weight and inflammation.